DARI PEMBERONTAKAN HINGGA DIPLOMASI: Menggali Peran Ulama dalam Politik Modern di Indonesia - Sugitanata, Arif (AL-BALAD : Jurnal Hukum Tata Negara dan Politik Islam, 2023)
This study aims to examine the role of the ulama in modern politics in Indonesia, focusing on the dynamics from rebellion to diplomacy. The research also analyzes the role of ulama using the political elite theories of Vilfredo Pareto and Gaetano Mosca to provide a new perspective on the power and influence of ulama in Indonesian politics. The methodology used is a literature review with a qualitative research approach, utilizing primary data from authoritative books, journals, and online sources. The results show that the ulama has a significant role in various aspects of Indonesian politics. In the early post-independence period, ulama such as Kyai Haji Hasyim Asy'ari played a role in mass mobilization against colonialists, while ulama like Abdurrahman Wahid (Gus Dur) used diplomatic strategies to maintain their influence despite efforts by the government to depoliticize religion. After the reform era, ulama gained a more significant space in politics, both through Islamic-based political parties and in their roles as advisors and mediators. The study also reveals that the ulama plays a crucial role in shaping public policies that reflect Islamic values. Fatwas issued by the Indonesian Ulama Council (MUI) often influence government policies in various fields, such as Sharia economics. Furthermore, ulama is involved in political education for the public, advocacy for marginalized groups, and participation in interfaith dialogue at international forums. Analysis based on Pareto and Mosca's political elite theories indicates that ulama is part of the elite holding moral and spiritual power and functions as advisors and mediators in practical politics. The process of elite circulation and the importance of religious organizations in maintaining their power highlight how the ulama continuously adapts and functions within the dynamic political power structure in Indonesia. With their long history of contribution and adaptation, ulama in Indonesia is poised to continue being a significant pillar in shaping the nation's political and social future.